2018
DOI: 10.1080/21688370.2018.1539596
|View full text |Cite
|
Sign up to set email alerts
|

The role of microtubules in the regulation of epithelial junctions

Abstract: The cytoskeleton is crucially important for the assembly of cell-cell junctions and the homeostatic regulation of their functions. Junctional proteins act, in turn, as anchors for cytoskeletal filaments, and as regulators of cytoskeletal dynamics and signalling proteins. The cross-talk between junctions and the cytoskeleton is critical for the morphogenesis and physiology of epithelial and other tissues, but is not completely understood. Microtubules are implicated in the delivery of junctional proteins to cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 166 publications
(213 reference statements)
3
57
0
Order By: Relevance
“…Similar off-centering has been observed in different conditions and the common underlying mechanism is considered to involve the stabilization of microtubules proximal to the intercellular junction and the capture and pulling of the centrosome towards the junction by those microtubules (Combs et al, 2006;Schmoranzer et al, 2009;Sipe et al, 2013). Indeed, microtubules and junctional adhesions mutually reinforce their stabilization (reviewed in (Vasileva and Citi, 2018)) (Chausovsky et al, 2000;Huang et al, 2011;Ligon et al, 2001;Meng et al, 2008;Shahbazi et al, 2013;Stehbens et al, 2006). Here we found that in early stages of EMT, microtubules were destabilized and the centrosome moved away from the junction.…”
Section: Discussionsupporting
confidence: 81%
“…Similar off-centering has been observed in different conditions and the common underlying mechanism is considered to involve the stabilization of microtubules proximal to the intercellular junction and the capture and pulling of the centrosome towards the junction by those microtubules (Combs et al, 2006;Schmoranzer et al, 2009;Sipe et al, 2013). Indeed, microtubules and junctional adhesions mutually reinforce their stabilization (reviewed in (Vasileva and Citi, 2018)) (Chausovsky et al, 2000;Huang et al, 2011;Ligon et al, 2001;Meng et al, 2008;Shahbazi et al, 2013;Stehbens et al, 2006). Here we found that in early stages of EMT, microtubules were destabilized and the centrosome moved away from the junction.…”
Section: Discussionsupporting
confidence: 81%
“…Apical microtubules contribute to the establishment and maintenance of apical and junctional domains (Feldman and Priess, 2012;Harris and Peifer, 2005;Vasileva and Citi, 2018), so losing apical microtubules during mitosis could weaken the integrity of an epithelial cell and make it more dependent on the PAR complex to maintain polarity. In Drosophila neuroblasts, parallel inputs from PAR complex proteins and microtubules assemble a polarized Pins/Gαi crescent to orient the mitotic spindle (Siegrist and Doe, 2005).…”
Section: Par Complex Protein Requirement During Epithelial Cell Mitosismentioning
confidence: 99%
“…ZO proteins also possess binding sites for actin (via the actin binding region), actin organizing proteins such as TOCA-1 (via the PDZ1 domain [47]), actinbinding proteins such as α-actinin-4 (via the PDZ-1 domain [48]) and cortactin (via a C-terminal domain [49]), and other cytoskeletal elements [see, e.g., 50,51]. These many-fold cis and trans binding events, both homophilic and heterophilic, support the hypothesis that the tight junction structure is a highly organized supramolecular complex of transmembrane and cytoplasmic proteins that is crosslinked to the actin cytoskeleton and, likely, to the microtubule network ( Figure 1a) [see, e.g., 40,52,53]. In addition, many studies have demonstrated posttranslational modifications of tight junction proteins, e.g., phosphorylation, correlated with changes in tight junction protein binding events and barrier function [see, e.g., 54,55,56,57,58,59].…”
Section: Tight Junction Proteinsmentioning
confidence: 79%
“…One interpretation of these data is that it suggests a disruption of the tricellular permeability barrier since manipulation of tricellulin levels in MDCK Type II renal epithelial cells (low TER) and HT29 intestinal epithelial cells altered the paracellular permeability of 4 kDa and 10 kDa fluorescein-dextran but not of 20 kDa fluorescein-dextran [62]. Incubation of T84 intestinal epithelial cells with a peptide comprising the distal half of the first extracellular loop of claudin-1 (Ser 53 to Thr 80 ) disrupted the tight junction localization of claudin-1, occludin, JAM-A, and ZO-1 and increased the paracellular permeability to both small ions (decreased TER) and large solutes (3 kDa fluorescein-dextran) [63]. Since the claudin-1 peptide dimerized in solution and bound to the extracellular domain of full-length claudin-1, it was proposed that claudin-1 homophilic interactions, either trans or cis, are critical for stabilizing the organization of tight junction proteins in the mature structure and, thereby, maintaining the paracellular permeability barrier.…”
Section: Which Proteins Form the Paracellular Permeability Barrier?mentioning
confidence: 99%